2010
DOI: 10.1097/brs.0b013e3181b7f1a7
|View full text |Cite
|
Sign up to set email alerts
|

Males With Familial Idiopathic Scoliosis

Abstract: Study Design Statistical analysis of genomic screening and fine mapping data. Objective The goals of this study were to analyze a region on chromosome 17 and to identify specific genetic determinants within this region linked to familial idiopathic scoliosis (FIS) in a subgroup of families in which affected males have undergone surgery. Summary of Background Data The high prevalence and variability of FIS is indicative of genetic heterogeneity. To localize genes related to scoliosis, identification of grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
(59 reference statements)
0
14
0
1
Order By: Relevance
“…This study mapped a region of approximately 20 cm on chromosome 17p11 linked to idiopathic scoliosis. Another study conducted by Clough et al, 11 in 2010, confirmed, by means of the linkage study, the relationship between the region described by Salehi et al 9 and familial idiopathic scoliosis, when studying 17 families with one member (proband) affected, of the male sex, who required surgical treatment to correct the deformity. Ocaka et al found chromosomal regions in chromosomes 9q34 and 17q25 2 …”
Section: Discussionmentioning
confidence: 70%
“…This study mapped a region of approximately 20 cm on chromosome 17p11 linked to idiopathic scoliosis. Another study conducted by Clough et al, 11 in 2010, confirmed, by means of the linkage study, the relationship between the region described by Salehi et al 9 and familial idiopathic scoliosis, when studying 17 families with one member (proband) affected, of the male sex, who required surgical treatment to correct the deformity. Ocaka et al found chromosomal regions in chromosomes 9q34 and 17q25 2 …”
Section: Discussionmentioning
confidence: 70%
“…We performed exome sequencing for a multigenerational family with familial IS and identified a potentially damaging and rare variant in the HSPG2 gene. Our previous linkage results were reviewed for potential correlation with the location of newly identified variants ( Miller et al 2005 , 2006 ; Alden et al 2006 ; Clough et al 2010 ; Marosy et al 2010 ). When this particular family was analyzed individually, marginal linkage signals were noted at nine loci (Miller, unpublished data, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The current literature includes multiple studies that have used linkage and association analyses. Genome-wide linkage analyses have effectively localized candidate regions; however, progress has been burdened by heterogeneity both within and between study populations and by insufficient statistical power ( Wise et al 2000 ; Chan et al 2002 ; Salehi et al 2002 ; Justice et al 2003 ; Miller et al 2005 , 2006 ; Alden et al 2006 ; Ocaka et al 2008 ; Gurnett et al 2009 ; Raggio et al 2009 ; Clough et al 2010 ; Marosy et al 2010 ; Edery et al 2011 ). Association studies, including genome-wide association studies (GWAS), have implicated select genes, including CHD7 , LBX1 , and GPR126 ( Gao et al 2007 ; Sharma et al 2011 ; Takahashi et al 2011 ; Kou et al 2013 ).…”
mentioning
confidence: 99%
“…Using this technique, Wise et al [ 14 ] in 2000, described the first regions related to AIS, on chromosomes 6p, 10q and 18q, after studying a large family with seven members affected by this disease. In the following years, other family studies have suggested that adolescent idiopathic scoliosis were related to chromosomes 6, 9, 16 and 17 [ 41 ], 17p11 [ 42 ], 19p13.37 [ 43 ], 8q12 [ 44 ], 9q31-q34.2 and 17q25.3-qtel [ 1 ], 12p23 [ 45 ] and 18q12.1-12.2 [ 46 ]. Wajchenberg et al [ 47 ] found no connection when studied a Brazilian family with multiple affected members.…”
Section: Reviewmentioning
confidence: 99%